2016
DOI: 10.1111/vru.12384
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Food Intake and Its Fat Composition on Intestinal Echogenicity in Healthy Dogs

Abstract: Dogs presenting for ultrasonography due to suspected gastrointestinal disease might have residual ingesta and this could have an affect on the appearance of intestinal mucosa unrelated to pathology. The purpose of this prospective descriptive study was to determine effects of a recent meal consisting of the recommended daily fat content (meal 1) and a higher fat one (meal 2) on mucosal echogenicity in healthy dogs. Sixty client-owned and clinically healthy dogs were recruited. Two meals, one with 15% fat dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 8 publications
(14 reference statements)
1
13
1
Order By: Relevance
“…This assumption is further supported by two recent studies, which demonstrated that oral administration of corn oil or a high‐fat diet could induce/increase similar hyperechoic mucosal changes ultrasonographically in healthy dogs and dogs diagnosed with lymphangiectasia. These transient ultrasonographic mucosal changes were suspected to reflect physiological postprandial lacteal dilation, and in one of these studies, the changes observed in healthy dogs overlapped the ultrasonographic findings described in dogs with lymphangiectasia and enteritis . This ultrasonographic finding should therefore be interpreted with caution, in relation with the clinical history and blood work of the patient, as well as delay between ultrasonographic examination and last meal.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This assumption is further supported by two recent studies, which demonstrated that oral administration of corn oil or a high‐fat diet could induce/increase similar hyperechoic mucosal changes ultrasonographically in healthy dogs and dogs diagnosed with lymphangiectasia. These transient ultrasonographic mucosal changes were suspected to reflect physiological postprandial lacteal dilation, and in one of these studies, the changes observed in healthy dogs overlapped the ultrasonographic findings described in dogs with lymphangiectasia and enteritis . This ultrasonographic finding should therefore be interpreted with caution, in relation with the clinical history and blood work of the patient, as well as delay between ultrasonographic examination and last meal.…”
Section: Discussionmentioning
confidence: 73%
“…Due to the lack of extensive history and blood work in the dogs included in this study, we cannot definitively conclude that these ultrasonographic findings were clinically nonsignificant. However, due to the minor histological changes associated with them, their high prevalence, the recent literature describing them as incidental findings, and the fact that most of these findings are commonly observed in a clinical setting at our hospital, in healthy dogs as well, it should also be considered that they could merely be associated with improved ultrasonographic transducer technology.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… suggested that increased mucosal echogenicity may be a more accurate indicator of IBD than intestinal wall thickness in dogs with chronic diarrhoea; however, a more recent study found that up to 50% of normal dogs had hyperechoic foci in the intestinal mucosa if scanned within 1 hour of a meal (Gaschen et al . 2016). Hence, the value of using this finding to help select further diagnostic tests is doubtful because it may not represent a pathological change.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, upper and lower gastrointestinal endoscopy may be employed regardless of ultrasound findings. Gaschen et al (2008) suggested that increased mucosal echogenicity may be a more accurate indicator of IBD than intestinal wall thickness in dogs with chronic diarrhoea; however, a more recent study found that up to 50% of normal dogs had hyperechoic foci in the intestinal mucosa if scanned within 1 hour of a meal ( Gaschen et al . 2016 ).…”
Section: Discussionmentioning
confidence: 99%